VISUALISASI REKOMENDASI PEMILIHAN JURNAL BIDANG INFORMATIKA DENGAN MENGGUNAKAN R DAN SHINY - Vega Purwayoga; Andi Nurkholis (Universitas Teknokrat Indonesia, 2023)
Lecturers are required to carry out the Tri Dharma, one of which is research. In the research process a lecturer sometimes encounters several obstacles. Some of the factors that become obstacles include incentives related to publication costs and the unavailability of appropriate journal references. Several ways to overcome obstacles in the publication process have been carried out, but there are still problems with lecturers being confused about publishing their scientific work in a journal. This obstacle is due to the absence of a journal selection recommendation system. This study recommends journals based on the scope of the journal, the number of editions of the journal, and the cost of publication of the journal. The recommendation process is carried out using a skyline query algorithm, namely Block-nested loop (BNL). BNL works by comparing domination between objects on an attribute. The object, in this case the journal, is recommended if the journal dominates several attributes or at least one attribute. This study also developed a visualization of journal recommendations in the form of a web-based application. This visualization is expected to facilitate the journal recommendation process to users, so that it can help find journals that are in accordance with the papers to be published in a journal.